GROWTH PERFORMANCE OF WHITELEG SHRIMP (Litopenaeus vannamei) AT DOC 90 IN DIFFERENT POND SHAPES UNDER INTENSIVE AQUACULTURE SYSTEM - Mukhammad Lukman Hakim .; Sri Oetami Madyowati; Achmad Kusyairi (Universitas Mataram, 2025)
This study aims to evaluate the effect of pond shape on the production performance of Litopenaeus vannamei in an intensive aquaculture system. Six ponds were used as experimental units, consisting of three square ponds (C1, C2, C3) and three circular ponds (C4, C5, C6), each stocked with 92,400 shrimp at an initial mean body weight (MBW) of 0.018 grams. Key parameters observed included initial biomass, final production, and average harvest yield. Results showed that circular ponds yielded higher production, with an average of 894 kg, compared to square ponds with an average of 758 kg. The Shapiro-Wilk normality test confirmed data normality, while the paired sample t-test indicated a statistically significant difference between the two pond shapes (p = 0.000). The superior performance of circular ponds is attributed to more uniform water circulation, efficient feed distribution, and optimized waste management. These findings highlight the importance of pond design in enhancing the productivity of L. vannamei under intensive farming conditions.